6 - Retour sur les conditions historiques et sociologiques de la fondation de la Tijâniyya - El Hadji Samba Amadou Diallo (Afrika Zamani, 2022)
Using the approach of historical sociology, this article analyzes the founding and diffusion of the Tijâniyya brotherhood. First, it describes how the founder Ahmad al-Tijânî was able to create a new path in Islam, encompassing both exogamic alliances and political strategies, by traveling widely geographically, transcending sub-regional frontiers. The result of these numerous travels was the quest for knowledge held by various men of God. The author proceeds to a theoritical synthesis of the mystical and ritual dimensions that made the creation of the Tijâniyya possible. Finally, the article sheds light on the process of delegating authority within the Tijâniyya during the XVIIIth Century.